IMPLEMENTASI FUNGSI POKOK PELAYANAN PRIMER PUSKESMAS SEBAGAI GATEKEEPER DALAM PROGRAM JKN (STUDI DI PUSKESMAS JUWANA KABUPATEN PATI) - Ainur Rahma; Septo Pawelas Arso; Anneke Suparwati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The National Health Insurance (NHI) program which embracing the principles of Managed Care, focuses on the health care needs of first level Health Care Provider, where the first level Health Care Provider have an important role because as the main gate of patients who need health care utilization (Gatekeeper), so hoppefully most of health services finished at primary level. Primary Health Center (PHC) as first level health facilitation have strategic role and advantages for supporting the implementation of NHI compared to family doctors and private clinics because it has two functions, that are the function of organizing Primary Health Efforts and Individual Health Efforts. Where the principal function of Individual Health Efforts in NHI as gatekeeper are strengthening the function of first contact care, continuity care, comprehensive care, and coordination care. The purpose of this study was to analyze implementation of 4 primary care principal function of PHC as gatekeeper in NHI program in Juwana PHC, Pati, guidelines with “Manual Pelaksanaan JKN-BPJS Kesehatan” and performance indicators